Ph prediction of sunshine mango using nir spectrometer - Woo, Pei Syan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
In this research, near-infrared (NIR) spectroscopy is a type of non-destructive methods that can be used to evaluate various internal quality attributes of fruits. pH is one of the important internal quality indices for mango fruits. However, the methods used to measure pH are still destructive. The aim of this research was to develop calibration model in predicting pH of Sunshine mangoes using NIR spectrometer. The transmission spectra of Sunshine mangoes were acquired in the wavelength range from 300 to 1000 nm.The effects of different types of pre-processing methods and spectra treatments, such as baseline correction, multiplicative scatter correction (MSC), Savitzky-Golay (SG) smoothing, second order derivative (SG) and normalisationwere analyzed. The prediction models were developed by partial least squares regression (PLS). The coefficient of determination (R2) of pH was 0.928 and the standard error of cross-validation (SECV) was 0.153 respectively. It is concluded that by using the NIR measurement system, in the suitable spectral range, it is possibleto predict the pH of mango fruits by non-destructively.